Associations of flavonoid intakes with metabolic dysfunction-associated steatotic liver disease in US adults - Yuwei He; Yu Chang; Xiangliang Liu; Yuguang Li; Wei Ji; Zhenyu Wang; Jiuwei Cui (PLoS ONE, 2025)
The incidence of Metabolic dysfunction-associated steatotic liver disease (MASLD) is rising annually. Dietary intervention is a cornerstone of MASLD management. Flavonoids, which have anti-inflammatory properties, are thought to benefit MASLD. Using data from the National Health and Nutrition Examination Survey (NHANES) from 2007–2010 and 2017–2018, we conducted a large cross-sectional study. Weighted Logistic regression, Restricted Cubic Spline (RCS) models, and Weighted Quantile Sum (WQS) regressions were used to explore the relationship between Total flavonoid and subclass (Flavones, Flavan-3-ols, Flavonols, Flavonones, Isoflavones, Anthocyanins) intake and MASLD. Participants in the higher tertiles of Total flavonoids intake had 31–34% lower odds of MASLD compared to the lowest tertile intake in the fully adjusted models (Tertile2: OR 0.69, 95%CI 0.55–0.86, P = 0.002, Tertile 3: OR 0.66, 95%CI 0.52–0.84, P < 0.001). Increased intakes of Flavan-3-ols (Tertile 2 in Model 2: OR 0.65, 95%CI 0.49–0.87, P = 0.01), Flavanones (Tertile 3 in Model 2: OR 0.70, 95%CI 0.53–0.91, P = 0.01), and Isoflavones (Tertile 3 in Model 2: OR 0.65, 95%CI 0.52–0.83, P < 0.001) were significantly associated with 30–35% decreased odds of having MASLD. The RCS revealed a significant non-linear dose-response relationship between Total flavonoid, flavonols and MASLD. The WQS model showed that Flavones and Isoflavones had the largest negative contributions to MASLD risk. Our study demontrated a negative correlation between Total flavonoids and their subclasses and risk of MASLD, highlighting the importance of increasing dietary flavonoid intake in the prevention and treatment of MASLD.